How do digital techniques of shape capture and alignment compare to traditional casting methods when applied to pediatric ankle-foot orthoses (AFOs)? - Connor Matton; Calvin C. Ngan; Jan Andrysek (PLoS ONE, 2025)
Achieving optimal alignment and fit is a key aspect of ankle-foot orthosis (AFO) design, as it directly influences the effectiveness of the device. While digital workflows offer the potential to integrate quantifiable alignment measures and corrections into AFO design, a major challenge remains in controlling lower-limb positioning and alignment during 3D scanning. This study aimed to evaluate pediatric AFO alignment and shape differences of directly scanned (live scan) vs casted lower limb models. Eighteen participants aged 4−16 years treated by 5 certified orthotists were recruited. Participants and casts were scanned. Sagittal plane ankle-foot alignment differences were analyzed between pairs of live scan and cast models. Using digital tools, the ankle-foot alignment of the live scans was then corrected, and the alignment differences were re-evaluated to assess the re-alignment methods and allow for further shape comparisons. After correction, modification maps were generated to assess the shape differences (surface deviations) between the live scans and cast models. Shape differences were also assessed with respect to participant characteristics. The results of this study demonstrated that AFO users can be scanned in a nearly corrected position (mean sagittal plane angle difference = 0.85°, SD = 4.44°), and that digital tools can be used to measure and adjust ankle-foot alignment with high accuracy (<1°error). The modification maps revealed that the live scans closely matched the cast models, with shape differences consistently observed in the foot and heel regions. Mean differences ranged −2.12–1.45 mm, positive differences (cast larger) ranged 1.14–2.71 mm, and negative differences (cast smaller) ranged 1.50–3.47 mm. Height, age, and foot length had moderate effects on shape differences (ρ = 0.5–0.75), while significant differences were observed between orthotists (∊2 = 0.32). These findings can drive future advancements in the digital design and fabrication of AFOs.